PENGARUH KUALITAS PRODUK, HARGA TERHADAP KEPUTUSAN PEMBELIAN DIMODERASI KEPUASANPADA KONSUMEN KEDAI ME & MOO - Vita Dyah Puspitasari, Erni Widajanti & Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this research is to analyze the significance of the influence ofproduct quality, price, consumers satisfaction to the purchase decision as well as theinfluence of product quality and price to the purchase decision with satisfaction as amoderating variable. The population is all consumerswho visit and buy at Kedai Me &Moo.100 respondents are selected as sample, using accidental sampling. This researchuses survey method, the type data collection with questionnaire and observation. Dataanalysis used test instruments, classic assumption test, multiple linear regressionanalysis,t test, F test, the coefficient of determination, and test the absolute value of thedifference. The result is there product quality dont have signifcants effect to thepurchase decision, price and consumers satisfaction have significance partially effect tothe purchase decision, consumers satisfaction didn’t moderate the effect of productquality and price to the purchase decision. Adjusted R2 on multiple linear regressionanalysis is 50,2% and adjusted R2 on test the absolute value of the difference each asmuch as 47,9% and 48,3%.Keywords: product quality, price, consumers satisfaction, purchase decision.